Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Karyawan Pesantren Terpadu Serambi Mekah - Imran, Imran (Jurnal Ekonomi, 2013)
Object of this study is on Serambi Mekkah Integrade Boarding School Padang Panjang to examine the effect of training and work motivation on employee performance Integrade Boarding School Serambi Mekkah Padang Panjang, to explain the concept of the relationship between the variable of training, motivation and performance. The purpose of this research is to determine how the model provides a more precides a more precise causal relationship between training, motivation and performance. The study population was Serambi Mekkah Integrade Boarding School employees Padang Panjang, a methode of making population sample of 130 people with purposive sampling number of 96 respondents were disributed. Analysis of the research data used is structurak aquation models with SPSS application program to test 2 (two) hypotheses thatÂ  have been developed, which ahs been hypothesized relationship is causal. And the result show that hypothesis 2 (two) hypothesis accepted this means training and motivation significant impact on employee performance Integrade Boarding School Serambi Mekkah. The result of this studies can also be shown that the variables that most influence on employee performance is variable and the next new motivational training, trus the managerial implication include efforts to improve employee motivation Integrade Boarding School Serambi Mekkah and efforts to improve employee training Serambi Mekkah Boarding School.